2018
DOI: 10.1055/s-0037-1612870
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of CD95 ligand protects the liver against ischemia-reperfusion injury and prevents acute liver failure

Abstract: Ischemia-reperfusion injury is a common pathological process in liver surgery and transplantation, and has considerable impact on the patient outcome and survival. Death receptors are important mediators of ischemiareperfusion injury, notably the signaling pathways of the death receptor CD95 (Apo-1/Fas) and its corresponding ligand CD95L. This study investigates, for the first time, whether the inhibition of CD95L protects the liver against ischemia-reperfusion injury. Warm ischemia was induced in the median a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…Recent studies have demonstrated the importance of the CD95/CD95L pathway to the nervous system, which is involved in the occurrence and development of a variety of neurological diseases such as AD, [38][39][40][41] but whether it is associated with neuropathic pain is not clear. The main function of CD95/CD95L is to participate in the immune response, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the importance of the CD95/CD95L pathway to the nervous system, which is involved in the occurrence and development of a variety of neurological diseases such as AD, [38][39][40][41] but whether it is associated with neuropathic pain is not clear. The main function of CD95/CD95L is to participate in the immune response, etc.…”
Section: Discussionmentioning
confidence: 99%